Forensic Identification of Suspected Poached Wild Boar (Sus scrofa affinis) - Patil, Sunil kumar; Shambhulingappa, Y.B.; Maheshkumar, S.; Jamuna, K.V.; Ramkrishna, V. (Journal of Buffalo Science, 2016)
A case of suspected wild boar death due to dynamite blast by poachers was received by us for confirmation. The skin sample was collected and examined histologically for identification based on hair follicle arrangement in the horizontal section of skin. The horizontal sections of skin from both domestic and wild boar was stained in order to study the distribution of hair follicles. Linear arrangement of hair follicles comprising three primary follicles in a row was observed in both domestic and suspected wild boar. Based on circumstantial evidence it was concluded that it may be belonging to wild boar.